ANALISIS EFEKTIVITAS PAJAK REKLAME TERHADAP REALISASI PENERIMAAN PAJAK REKLAME DI KABUPATEN MADIUN - Dinda Ayu Prameswara; La Ode Abdullah (Gapenas Publisher, 2022)
Regional Original Income (PAD) is income sourced from tax collection, one of which is the Billboard Tax. Billboard Tax in Madiun Regency has increased and decreased in the last 5 years. The decline was caused by several things, including the loss of potential Advertising Tax, and the existence of taxpayers who did not pay or were late in paying tax contributions. The purpose of this research activity is to determine the level of effectiveness between the realization of revenue receipts and the target of Advertising Tax revenue and its contribution to PAD in Madiun Regency for the 2016-2020 tax period by calculating using the formula for analyzing the effectiveness and contribution level. The method carried out in this study is a quantitative method. The analytical tools used in this study are, the realization of Advertising Tax revenue, the target of Advertising Tax revenue, the Realization of Regional Original Income. The benefits of this research activity are, as a means of evaluation for BAPENDA, especially related to Advertising Tax. The result of this study is the effectiveness of Advertising Tax revenues on the realization of Billboard Tax revenues in Madiun Regency during the 2016 tax period is considered to be